Evaluasi Kinerja Manajemen dan Keuangan Pemerintah Provinsi Sumatera Selatan Tahun Anggaran 2014-2018 - Dwi Riana (Politeknik Negeri Sriwijaya, 2021)
This research aims to study the management and financial performance of the Government of South Sumatra in 2014-2018. This research is quantitative descriptive. The research used secondary data from the financial report of South Sumatra for 2014-2018 and other supporting data sourced from the Regional Financial Management Agency (BPKD) of the South Sumatra Government. The analysis technique used in this study is to calculate and analyze the financial ratios to the APBD that have been implemented. Based on the results of data processing and discussion of the results of the study, the South Sumatra Government's financial year for 2014-2018 was good enough. While the average independence ratio is 39.06% included in the consultative relationship pattern, the average efficiency ratio of 92.38% is included in the effective criteria, the average acquisition ratio is 74.87% included in the efficient criteria. Furthermore, the average ratio of operating expenditure activities was 79.62% and the average ratio of capital expenditure activities was 19.43%. When viewed from the activity ratio, the Government of South Sumatra prioritizes operating expenses over capital expenditure. In addition, the growth ratio from 2014-2018 showed fluctuating results.